A book takes root : the making of a picture book - Kehoe, Michael (Minneapolis : Carolrhoda Books, 1993)
Traces the process of making a picture book, from idea to manuscript to final publication.
Keywords: Picture books for children -- United States; Picture books; Books; Authorship